The Effect of Lithium Doping on the Sintering and Grain Growth of SPS-Processed, Non-Stoichiometric Magnesium Aluminate Spinel - Mordekovitz, Yuval (Materials (Basel), 2016)
The effects of lithium doping on the sintering and grain growth of non-stoichiometric nano-sized magnesium aluminate spinel were studied using a spark plasma sintering (SPS) apparatus. Li-doped nano-MgO·nAl(2)O(3) spinel (n = 1.06 and 1.21) powders containing 0, 0.20, 0.50 or 1.00 at. % Li were synthesized by the solution combustion method and dense specimens were processed using a SPS apparatus at 1200 °C and under an applied pressure of 150 MPa. The SPS-processed samples showed mutual dependency on the lithium concentration and the alumina-to-magnesia ratio. For example, the density and hardness values of near-stoichiometry samples (n = 1.06) showed an incline up to 0.51 at. % Li, while in the alumina rich samples (n = 1.21), these values remained constant up to 0.53 at. % Li. Studying grain growth revealed that in the Li-MgO·nAl(2)O(3) system, grain growth is limited by Zener pining. The activation energies of undoped, 0.2 and 0.53 at. % Li-MgO·1.21Al(2)O(3) samples were 288 ± 40, 670 ± 45 and 543 ± 40 kJ·mol(−1), respectively.